Exploring the Relationship Between Reading Interest and Comprehension Skills in Grade IV Students: A Study on Children's Literature - Dinda Febrianita Resitaningrum; Bambang Saptono (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study explores the initial low reading interest and comprehension skills of fourth-grade students at Bintaran Elementary School and the impact of using children’s literature to address these issues. A qualitative descriptive approach was employed to provide an in-depth analysis of students' reading habits and comprehension abilities. Data were collected through interviews, observations, questionnaires, and documentation to capture a comprehensive picture of the situation. Findings revealed that students exhibited a low interest in reading, characterized by a general dislike of books, which directly impacted their reading comprehension skills. After the integration of children’s literature into the curriculum, students demonstrated improved engagement and comprehension. Teachers employed strategies such as book-reading competitions to motivate students, fostering both enjoyment and understanding of reading materials. The results highlight the importance of cultivating reading interest and comprehension skills in students to facilitate knowledge acquisition and the development of competencies essential for lifelong learning. Children’s literature emerged as an effective medium for enhancing these abilities, providing an engaging and relatable context for students. The use of children’s literature significantly improves reading interest and comprehension among elementary students. Future studies should explore the long-term effects of this approach and its application across diverse age groups and educational settings.